PROFIL PEMECAHAN MASALAH TEOREMA PYTHAGORAS DITINJAU DARI PERBEDAAN GAYA KOGNITIF SISWA - Aryanugraha Alnar; Ilham Minggi; Randy Saputra Mahmud; Ahmad Syamsuadi; Fathrul Arriah (Jurnal Riset Guru Indonesia, 2022)
One of the abilities to be achieved through learning mathematics is the ability to solve problems. The problem is not just found in mathematics but also in their daily activity. The student needs to know how to solve a problem because there are many problems in the future that they must solve. Problem-solving in every student is different. The cause is the cognitive style that the student has. The student receives, manages, and makes the conclusion according to their cognitive style. The study aims to describe students' mathematical problem-solving abilities on the Pythagorean theorem material concerning field-independent and field-dependent cognitive styles. The method uses a qualitative descriptive approach with problem-solving test instruments, interview guidelines, and GEFT tests. Determination of the subject using the GEFT test to obtain a subject with an independent field of cognitive style and independent field of 2 subjects each. Problem-solving tests and interviews were used to obtain data on the subject's problem-solving abilities. The problem-solving indicator used is based on Polya's theory. The results showed that the subject with independent field cognitive style was able to do problem-solving well. While the subject with a field-dependent cognitive style is quite capable of solving problems, this is because there are some mistakes in writing answers. However, based on the interview, it was found that the subject was able to solve the problem but was in a hurry to solve the problem.